Early maladaptive schemas and aggressiveness in high school students from Lima Metropolitan Area - Collado Osorio, Lizbeth Pamela (2019)
This research aimed to establish the relationship between early maladaptive schemas and aggressiveness. The sample consisted of 641 fourth- and fifth-year high school students aged 14 to 18 from Lima Metropolitan Area. The study had a descriptive, correlational and comparative design. The Buss-Perry Aggression Questionnaire (1992) and the Young Schema Questionnaire Long Form - Second Edition (YSQ-L2) were used in the study. The results show a significant and positive relationship between early maladaptive schemas and aggressiveness. At the descriptive level, the most prevalent schemas were emotional deprivation and insufficient self-control/self-discipline. On the aggressiveness scale and subscales, the results showed average levels, with the exception of the anger component, which had a low score.